1991
DOI: 10.1182/blood.v78.11.3066.bloodjournal78113066
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal dominant erythrocytosis caused by increased sensitivity to erythropoietin

Abstract: We describe here a family with autosomal dominant erythrocytosis. In in vitro cultures, performed using the methyl cellulose assay, the number of erythroid colonies was normal or marginally increased when a standard concentration of erythropoietin (Epo) was used, but at lower Epo concentrations, the investigated persons formed more colonies than the controls. The difference was generally greater the lower the Epo concentration became. Some erythroid colony growth was seen even in the absence of any added Epo (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 0 publications
1
40
1
Order By: Relevance
“…The cells from Granulocyte-Macrophage Colony Forming Unit (CFU-GM), Granulocyte-CFU (CFU-G), Macrophage-CFU (CFU-M), and erythroid-burst forming units (BFU-E) colonies were obtained from the in vitro cultures of normal human bone marrow mononuclear cells (MNC) cultured for routine purposes as previously described (Juvonen et al, 1991). The CFU-GM, CFU-G, CFU-M or BFU-E colonies were identified by inversion microscopy, based on the typical morphology or red colour of the cells, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The cells from Granulocyte-Macrophage Colony Forming Unit (CFU-GM), Granulocyte-CFU (CFU-G), Macrophage-CFU (CFU-M), and erythroid-burst forming units (BFU-E) colonies were obtained from the in vitro cultures of normal human bone marrow mononuclear cells (MNC) cultured for routine purposes as previously described (Juvonen et al, 1991). The CFU-GM, CFU-G, CFU-M or BFU-E colonies were identified by inversion microscopy, based on the typical morphology or red colour of the cells, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Recent experiments have demonstrated that both tyrosines are responsible for binding of SHIP-1 to EpoR (Yi et al, 1995). Primer positions are also indicated by the arrows in the figure. these patients to erythropoietin, which has been demonstrated at low Epo levels in other PFCP families (Prchal et al, 1985;Juvonen et al, 1991;Sokol et al, 1995).…”
Section: Study Of Erythroid Progenitorsmentioning
confidence: 58%
“…Affected family members do not usually need any specific treatment for their polycythaemia and their degree of erythrocytosis has remained remarkably stable (Prchal et al, 1985;Emanuel et al, 1992). In vitro cultures have demonstrated an increased sensitivity of erythroid progenitors from these family members, although no erythroid colonies formed in cultures without erythropoietin (Epo) ( Juvonen et al, 1991;Sokol et al, 1995). Erythrocytosis in these families has been demonstrated to be significantly linked with erythropoietin receptors (EpoR), via the detection of a simple sequence repeat polymorphism in the EpoR (Sokol et al, 1993Chapelle et al, 1993a).…”
mentioning
confidence: 99%
“…A cross-country skier who won several Olympic gold medals was initially accused of doping. However, it was later determined that he had an autosomal dominant mutation in his EPO receptor resulting in erythrocytosis and haematocrit levels up to 68% (Prchal et al, 1985;Juvonen et al, 1991) (for comparison, the normal haematocrit range is 39-45%). Considerations must be made to avoid inappropriate sanctioning of athletes who, through genetics or physiology, test positive for doping.…”
Section: Testing Strategiesmentioning
confidence: 99%